An Analysis of figurative Language in Banda Neira’s Album Yang Patah Tumbuh, Yang Hilang Berganti - Maghfirah Fitri MG; Kismullah Kismullah; Chairina Nasir (Universitas Syiah Kuala, 2022)
Figurative language is a way of expressing language feelings. This research discusses the analysis of figurative language in Banda Neira’s album yang patah tumbuh, yang hilang berganti. The purpose of this study to determine the types of the figurative language contained in the album. Besides, the researcher also explained the real meaning, the message contained in the song and mentioned the theme of each song. The source is taken from Banda Neira's album